Análise da concentração de elementos traço em bases faciais por fluorescência de raios X - Nogueira, Camila Sampaio (2024)
Facial foundations are cosmetic products widespread in the beauty and personal care sector and are present in the routine of many people. In recent years, research involving elemental analysis of cosmetics has received attention from the scientific community, as the presence of elements harmful to health in cosmetic formulations may occur due to natural contamination of the raw material or manufacturing processes. Therefore, national and international regulatory agencies have resolutions that seek to regulate the presence of heavy metals and trace elements in cosmetics. In alignment with the resolution of the European Parliament and the Council, the National Health Surveillance Agency (ANVISA) prohibits the presence or restricts the concentration of elements such as As, Ba, Be, Br, Cd, Cl, Co, Cr, Hg, I, Nd, Ni, P, Pb, Sb, Se, Te, Tl and Zr in cosmetic formulations due to their toxicological implications in contact with the skin, eyes and oral cavity. Therefore, this work aimed to determine the concentration of trace elements in facial foundation samples using the X-ray fluorescence technique to verify whether they comply with the resolutions proposed by ANVISA. For this, 51 samples of fluid facial foundations were purchased from cosmetics stores in Curitiba and São Paulo. Data was collected using an X-ray fluorescence kit composed of an X-ray tube with an Ag target (Model Mini-X) and a silicon semiconductor detector (Model X-123SDD) sold by Amptek Inc.®. The elements Cr, Ni, Cu, Zn, Br, Rb, Sr, Zr, Cd, and Ba were quantified using the standard addition method combined with scattered X-ray calibration and standardization methods. The results showed that all the quantified elements disagree with the regulations set out by ANVISA. Of the quantified elements that comprise the regulatory agency’s list of prohibited elements, only Cr and Sr did not present concentrations above 100 µg/g, the maximum value established for the contamination of metals in artificial colorings. Cd and Ni, elements recognized as harmful to health, presented maximum concentrations of 277 ± 51 µg/g and 130 ± 10 µg/g, respectively. Regarding the restrictions proposed by ANVISA, the highest concentration determined for Zr reached 589 ± 57 µg/g, approximately six times above the established limit. In contrast, Ba concentrations exceeded 14 thousand µg/g, approximately 60 times above the limit, with the highest concentration reaching 30,867 ± 1,500 µg/g. This research contributes to expanding knowledge about the presence of elements potentially harmful to health in the facial foundation, in addition to pointing out the disagreements between cosmetics sold in the country and the resolutions proposed by ANVISA.